Assessment and Map Analysis of the Terrain and Landscape for the Siting of Banks Locations in Abaji Area of Abuja Federal Capital Territory, Nigeria - AYADIUNO, ROMANUS UDEGBUNAM; ODILAMMA, AGBAKWURU GLORY; NDULUE, DOMINIC CHUKWUKA (The journal of contemporary issues in business and government, 2021)
Land is the centre point of human existence and development. Development is achieved through modernization, improvement of infrastructure, financial systems and agriculture. In any economy, the financial system plays active role in production. Banks are seen as agents of development. This work is aimed at assessing and identifying optimal locations to site new banks in Abaji L.G.A of Abuja Federal Capital Territory, Nigeria. It seeks to examine the distribution patterns of existing banks and the factors necessary for the location of banks. GIS analysis was done in ArcGIS software to analyze maps extracted from satellite imageries. Nearest neighbour analysis was used to explain the pattern of distribution of banks within the study area while proximity analysis was also carried out to assess the distance of major population areas to the banks. Both primary and secondary data were used in extracting information from the study area. The study also used quantitative and qualitative methods in analyzing and presenting the numerous factors for siting banks loctions. Descriptive and inferential statistics were used to analyse demographic characteristics of the respondents. Results from analysis shows that banks in Abaji L.G.A are in a regular pattern and they only exist within Abaji town leaving out other areas in the study area leading to increase in the number of the financially excluded populace. Overlay technique was used for all the variables that were analyzed, this makes for proper identification of suitable locations for sitting of banks in the study area. The recommendations therefore are among others, increase in the number of banks in Abaji L.G.A as population increases, establishing the mediums to aid in the establishment of banks and other banking facilities.